A case with unilateral hypoglossal nerve injury in branchial cyst surgery - Mukherjee, Sudipta Kumer; Gowshami, Chandra Bidhan; Salam, Abdus; Kuddus, Ruhul; Farazi, Mohshin Ali; Baksh, Jahid (Journal of Brachial Plexus and Peripheral Nerve Injury, 2012)
An 11 years old boy came, with complain of mild dysarthria. Examination revealed marked hemiatrophy of left side of the tongue. Five months back he underwent ipsilateral branchial cyst operation. To our knowledge, no case was reported. After branchial cyst operation if there is any residual remnant chance of recurrence is very high.
Keywords: Hemiatrophy; Hypoglossal nerve; Brancial cyst